Mutagenesis : exploring novel genes and pathways - Tomlekova, N. B., editor; Kozgar, M. I. (Mohammad Imran), editor; Wani, M. R. (Mohd Rafiq), editor (Wageningen, Netherlands : Wageningen Academic Publishers, 2014)
Includes bibliographical references and indexes